PENGARUH KEPEMIMPINAN DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI: PERAN MEDIASI MOTIVASI KERJA - Haryono, Siswoyo; Febriansyah, Febriansyah; Sumarni, Saptaningsih (Universitas Muhammadiyah Surakarta, 2020)
Human resources have a major role in organizational activities, to mobilize and synergize other resources in achieving organizational goals. Employees together with leaders determine work goals, standards of achievement that must support and assess the results of achievement. The study of leadership, work skills, work motivation, performance is important for evaluation. This study aims to understand leadership, work ability on performance, the South Sumatra Provincial Education Office mediated by work motivation. The research sample was 255 people and the sampling technique used purposive sampling. Data were collected using the method of observation and questionnaire, and analyzed using structural equation modeling. The results obtained that the variables of leadership, work ability on work motivation, and work motivation support employee performance. Besides the leadership variable, work ability also influences employee performance.